Precise Purity Analysis of High-Purity Lanthanum Oxide by Gravimetric Analysis Assisted With Trace Elemental Analysis by Inductively Coupled Plasma Mass Spectrometry - Miura, Tsutomu; Wada, Ayaka (Frontiers in Chemistry, 2022)
Gravimetric analysis was used to determine the purity of high-purity La2O3 by stepwise conversions of the weighing forms. In this study, lanthanum in the sample was converted to La oxalate, La2O3, and La2(SO4)3, to evaluate the stoichiometry of the weighing forms for accurate gravimetric determination. The losses of La in the filtrate, the washing solution of the precipitate and the mechanical loss of La during filtration were measured by inductively coupled plasma optical emission spectrometry. The weighing forms were evaluated by comparing the observed mass ratio with the theoretical value at each conversion step. The final converted La2(SO4)3 was consistent with the theoretical composition based on the observed mass ratio of La2(SO4)3/La2O3. Additionally, impurities in the high-purity La2O3 were determined by inductively coupled plasma tandem mass spectrometry. The purity of the original La2O3 sample was precisely determined to be 99.977 % ± 0.057 % (mass fraction as La2O3; the value following “±” indicates the expanded uncertainty with a coverage factor k=2.18) by a combination of gravimetric analysis using the precipitation from homogeneous solution method and verification of the weighing forms for La compound.